A three-dimensional numerical method to study pipeline deformations due to transverse impacts from dropped anchors. (June 2016) - Yu, Jian-xing; Zhao, Yi-yu; Li, Tian-yu; Yu, Yang
Abstract: The transverse impact on a pipeline caused by a dropped anchor is among the main factors resulting in submarine pipeline failure. The impact could cause leakage of the pipeline, resulting in a huge environmental disaster and heavy economic losses. To investigate the deformations of a pipeline impacted by dropped anchors, a three-dimensional numerical method, known as the local Galerkin discretization method for shell structures, is developed under the condition of a rigid bed. The method has the advantages of higher-order resolution and low computational cost. Small-scale model experiments were then carried out. Different bed conditions were considered, including rigid ground and ground covered by sandy soil. The dent depths of the pipes after the impacts were measured to study the pipeline deformations. The dent depths estimated by the local Galerkin discretization method were compared with the results of the experiment, which showed good consistency. The Galerkin numerical simulation method can also be applied to other pipe impact situations. Highlights: A three-dimensional numerical method for studying pipeline deformations is developed. The method has the advantage of higher-order resolution and low computational cost. We conducted test to investigate pipeline deformations impacted by dropped anchors. The dents of pipeline depend on impact energy and contacting area.